Identifying the most common types, causes and locations of Injuries between Students - Abdulrahman, Chyavan Mohammed (Academic Journal of Nawroz University, 2020)
The current research aims to Identify the most common types of sports injuries that occurring to students of the Faculty of physical Education at University of Duhok, Identifying the most areas of the body that exposed to this injuries and most important reasons that lead to these injuries among students. A questionnaire was designed for the study included three tables, the first table includes common types of injuries, the second table included the common reasons that lead to injuries and the third table included the most common areas of the body exposed to injuries. The reliability and the validity of the questions were evaluated. The researcher has used descriptive method .The sample of research included injured students of the faculty of Physical Education . The survey included a total sample of 675 students .The total number of sports injuries from both gender reported of the all four-stages students in the college that covered by the study was 98 (14.51%) .Data were collected from the questionnaires and SPSS version 22 was used to analyze them . the result show that Knee injuries were the most areas of the body exposed to injury for physical education students, the muscle rupture injuries were the most common type of injurie and warming-up was one of the main causes of injuries.